Aspek Perkembangan Sosial Emosional Anak Usia 6 Tahun Melalui Instrumen Asesmen Skala Penilaian - Fitri, Cinta Atmaditia; Julafni, Mia; Pasaribu, Nuraisyah; Tria, Reza Ade; Zahara, Siti; Zahiroh, Zalfa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to identify the level of social-emotional development in 6-year-old children using an assessment instrument in the form of a rating scale. Social-emotional development is a crucial aspect of early childhood that includes emotional regulation, the ability to form healthy social relationships, and prosocial behavior. This research employed an interview method with a participatory observation approach involving six children from a kindergarten in Medan. Data were collected using a rating scale instrument based on social-emotional development indicators. The results showed that most children were in the Developing as Expected (BSH) category, especially in cognitive, language, and social-emotional aspects. However, some children were still in the Starting to Develop (MB) category in terms of independence. This study highlights the importance of holistic assessments to fully understand children's developmental needs.